An integrative action research on implementing a customer relationship management (CRM) for effective lead maintenance, account management, and after-sales documentation - Bibi, Aibar Rabi Rashad (Animo Repository, 2023)
This action research addressed the challenges faced by our company, GoPrime Technology Corp. doing business as GoSolar Philippines, which specializes in providing clean and sustainable solar power systems. Our organization relied on multiple decentralized records stored in Google Sheets and Microsoft Excel for managing our customer data, leading to issues such as billing errors, data privacy concerns, and inconsistent client records. To overcome these challenges, I as the researcher, together with my collaborators, proposed the implementation of a Customer Relationship Management (CRM). To guarantee the effectiveness of the interventions, we employed the CRM framework for developing the core features and functionalities of the system, along with implementing Lewin's change model during our initial roll-out. The research followed a two-cycle approach: a) the first cycle focused on successfully launching the CRM, and b) the second cycle centered on obtaining user feedback that was used to further improve the system. The successful CRM implementation equated to enhanced operational efficiency, improved customer satisfaction, and captured financial success. At the end of the two cycles, we have established the success metrics monitoring for the continuous improvement of the system even after the end of the research cycles. Overall, the study demonstrated the significance of implementing a CRM to address the issues at hand and the opportunities associated with the automation, reporting, and monitoring of data from the CRM.